Age at first child: intra-generational distances in Uruguay - Filardo, Verónica (Papeles de Población, 2018)
One of the paradigmatic events of the transition to adulthood is having the first child since an adult role par excellence is that of father or mother. The age at which the first child is had, influences the trajectories (labor, education) of young people; although also differences are marked by gender, educational attainment, region of residence and conjugal experience. This paper studies the beginning of the reproductive life of adolescents and young people in Uruguay, using a set of techniques of data analysis and using as a source the National Survey of Adolescents and Youth applied to urban youth in Uruguay in 2013.